2014
DOI: 10.7202/1021981ar
|View full text |Cite
|
Sign up to set email alerts
|

Greywater Characteristics In Rural Areas of the Sahelian Region for Reuse Purposes: The Case of Burkina Faso

Abstract: The characteristics of greywater generated in two rural areas (“Barkoundba” and “Kologoudiessé”) located in the Sahelian region in Burkina Faso were assessed through observations in selected concessions, sample collection and laboratory analyses. The study aimed at characterizing the qualitative and quantitative characteristics of greywater in order to evaluate its reuse potential for gardening in rural areas. The results showed that greywater is generated from 3 to 4 main sources with average daily production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The presence of phosphates and nitrates in greywater has been attributed to detergents and washing powders [16]. The nutrient content in the influent is in the range of reported values from Burkina Faso [15]. (Table 1; Figure 5).…”
Section: Nutrient Removalmentioning
confidence: 76%
See 2 more Smart Citations
“…The presence of phosphates and nitrates in greywater has been attributed to detergents and washing powders [16]. The nutrient content in the influent is in the range of reported values from Burkina Faso [15]. (Table 1; Figure 5).…”
Section: Nutrient Removalmentioning
confidence: 76%
“…The values were varying from 14 to 88 mg/L for SS, 65 to 170 mg/L for BOD 5 and 145 to 958 mg/L for COD ( Table 2). In rural area, for shower, laundry and dishwashing greywater, mean values of 1093 to 3060 mg/L, 533 to 2743 mg/L and 1240 to 6497 mg/L have been reported for SS, BOD 5 and COD respectively [15]. This situation could find an explanation in the effect of dilution due to the differences in amounts of water used to perform the activities.…”
Section: Physico-chemical Characteristics Of the Raw Greywatermentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, the results of pollutant load analysis in the raw greywater showed that the mean values of TSS, COD and BOD5 was 416.67 mg/L, 346.33 mg/L and 216.47 mg/L, respectively, and was relatively higher as compared those of treated greywater. However, these pollutant loads were less polluted in terms of organic matter pollution than mixed laundry-dishwashing greywater (SS = 1230 mg/L, COD = 3916 mg/L and BOD5 = 1375 mg/L) reported by Maiga et al (2014). BOD and COD concentrations in greywater strongly depend on the amount of water and products (especially detergents, soaps, oils and fats) used in the household (Morel and Diener, 2006).…”
Section: Raw Greywater and Treated Greywater Characteristicsmentioning
confidence: 99%
“…The mean values in the raw dishwashing greywater were from 2.78× 10 5 CFU/100 mL, 1.15 × 10 5 CFU/100 mL for E. coli and fecal coliforms, respectively (Table 1). The highest values of up to 2.3 × 10 7 CFU/100 mL for E. coli and up to 3 × 10 7 CFU/100 mL for fecal coliforms have been reported from dishwashing of household in rural area (Maiga et al, 2014). Fecal contamination in dishwashing greywater is due to contaminated vegetables and raw meat used during the cooking process (Ottosson, 2003).…”
Section: Raw Greywater and Treated Greywater Characteristicsmentioning
confidence: 99%